2014
DOI: 10.1111/dme.12347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetic neuropathy on foot bones: a systematic review and meta‐analysis

Abstract: We did not find a significant relationship between presence of neuropathy in those with diabetes and poorer peripheral bone health. However, methodological limitations of the included studies mean further research is required to investigate this theoretical relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Several studies have demonstrated a reduction in calcaneal bone density assessed by ultrasound in association with the presence of peripheral sensory neuropathy (Conti et al, 2010;Rix, Andreassen, & Eskildsen, 1999;Sieradzki, Trznadel-Morawska, & Olszanecki, 1995). However, more recent studies have not reproduced this relationship (Barbaro, Orsini, Lapi, Turco, & Pasquini, 2008;Chakrabarty et al, 2004;Christensen, Bulow, Simonsen, Holstein, & Svendsen, 2010), and meta-analysis of existing data does not support such an association (Barwick et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have demonstrated a reduction in calcaneal bone density assessed by ultrasound in association with the presence of peripheral sensory neuropathy (Conti et al, 2010;Rix, Andreassen, & Eskildsen, 1999;Sieradzki, Trznadel-Morawska, & Olszanecki, 1995). However, more recent studies have not reproduced this relationship (Barbaro, Orsini, Lapi, Turco, & Pasquini, 2008;Chakrabarty et al, 2004;Christensen, Bulow, Simonsen, Holstein, & Svendsen, 2010), and meta-analysis of existing data does not support such an association (Barwick et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies examining the relationship between neuropathy and the development of Charcot foot are inconclusive (Barwick et al, 2014). Several studies have demonstrated a reduction in calcaneal bone density assessed by ultrasound in association with the presence of peripheral sensory neuropathy (Conti et al, 2010;Rix, Andreassen, & Eskildsen, 1999;Sieradzki, Trznadel-Morawska, & Olszanecki, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Final group allocation was based on the average of bilateral VPT with peripheral neuropathy defined at or above 25 V. The threshold of 25 V is commonly used in clinical studies to indicate high risk of foot ulceration [ 16 ], and a VPT above this threshold is abnormal irrespective of age [ 17 ]. The sample size was set at 20 participants per group based on previous similar studies [ 18 ]; however, ultimately the COVID-19 pandemic hindered recruitment.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that endothelial nitric oxide and other endothelium-derived agents such as prostaglandins and endothelium-derived hyperpolarising factors play a role in the mechanism of PORH [63]. Apart from these substances, the sensory nerves contribute to the PORH mechanism, which makes this test suitable to assess neurovascular responses [20,[62][63][64][65][66][67]. The test involves recording a baseline reading, followed by an occlusion using supra systolic pressure (~180 to 220 mmHg) for a certain period and release of pressure.…”
Section: Post-occlusive Reactive Hyperemiamentioning
confidence: 99%